2012
DOI: 10.1039/c2dt31570j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antitumor activity of new ferrocene incorporated N,N′-disubstituted thioureas

Abstract: We report herein the synthesis, structural characterization and activity against human ovarian tumour models: A2780 (parent), A2780(cisR) (resistant to cisplatin) and A2780(ZD0473R) (resistant to the cisplatin analogue denoted as ZD0473) of two ferrocene incorporated N,N'-disubstituted thioureas {1-benzoyl-3-(4-ferrocenylphenyl)thiourea, B16, and 1-acetyl-3-(4-ferrocenylphenyl)thiourea, B3}. Structural characterization has been based on FT-IR, multinuclear ((1)H and (13)C) NMR, elemental analysis and single cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Phenyl derivative (R1=H, R2=Ph) of the series shows intercalation but methyl derivative shows electrostatic interaction. [41] Six novel ferrocenyl thioureas (R1=CH3, R2=CH3, -CH(CH3)2, -CH2C6H5, -CH2Cl, -C2H5, -C(CH3)3) were prepared, their DNA binding abilities and anti-oxidant properties were investigated. It was found that some compounds showed strong electrostatic interaction with DNA in its oxidized form rather than in reduced form.…”
Section: K) Thioureas As Dna Bindermentioning
confidence: 99%
“…Phenyl derivative (R1=H, R2=Ph) of the series shows intercalation but methyl derivative shows electrostatic interaction. [41] Six novel ferrocenyl thioureas (R1=CH3, R2=CH3, -CH(CH3)2, -CH2C6H5, -CH2Cl, -C2H5, -C(CH3)3) were prepared, their DNA binding abilities and anti-oxidant properties were investigated. It was found that some compounds showed strong electrostatic interaction with DNA in its oxidized form rather than in reduced form.…”
Section: K) Thioureas As Dna Bindermentioning
confidence: 99%
“…In this struggle tremendous attention has been given to the ferrocene and its derivatives. Ferrocene [2], nitrophenyl ferrocene [3], antimony derivatives of ferrocene [1] and thiourea [4] and selenourea derivatives of ferrocene [5][6][7] have been evaluated for their interactions with DNA. It has been observed that almost all the derivatives of ferrocene have higher drug-DNA binding constant than simple positively charged ferrocene moiety (3.45 x 10 2 M -1 ) although when these derivatives are not coupled with ferrocene then they are themselves less active for DNA.…”
mentioning
confidence: 99%
“…It should be mentioned that the screening of the iron atom by two bulky ligands minimize the influence of the solva tion effects on the oxidation and reduction potentials of the substrates, which often results in the absence of a de pendence of the oxidation potential on the nature of the solvent used. Interest in ferrocene derivatives is due to their use in pharmacology, in particular, for the treatment of oncology, diabetes, malaria, and other infection dis eases 17, 18 and applications in petrochemistry 19 Ferrocene derivatives 2-9 were studied by CV in 1,2 di chloroethane containing Bu 4 NPF 6 as a supporting elec trolyte (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%